Experimental evaluation of the mechanical degradation of HPAM polymeric solutions used in enhanced oil recovery (2020)
With the design of experiments (DoE), this study analyses the influence of physical (capillary diameter and pressure drop) and chemical variables (salinity, polymer concentration, and molecular weight) on the mechanical degradation of partially hydrolyzed polyacrylamide-type polymer solutions (HPAM) used in enhanced oil recovery processes. Initially, with the help of a fractional factorial design (2k-p), the variables with the most significant influence on the polymer's mechanical degradation were found. The experimental results of the screening demonstrate that the factors that statistically influence the mechanical degradation are the molecular weight, the diameter of the capillary, and the pressure differential. Subsequently, a regression model was developed to estimate the degradation percentages of HPAM polymer solutions as a function of the significant factors influencing the mechanical degradation of polymer solutions. This model had a 97.85% fit for the predicted values under the experimental conditions. Likewise, through the optimization developed by the Box Behnken response surface methodology, it was determined that the pressure differential was the most influential factor. This variable was followed by the capillary diameter, where less than 50% degradation rates are obtained with low polymer molecular weight (6.5 MDa), pressure differentials less than 500 psi, and diameters of the capillary greater than 0.125 inches.